Expansion and preservation of the functional activity of adult hematopoietic stem cells cultured ex vivo with a histone deacetylase inhibitor - Zimran, Eran; Papa, Luena; Djedaini, Mansour; Patel, Ami; Iancu‐Rubin, Camelia; Hoffman, Ronald (Stem cells translational medicine, 2020)
Attempts to expand ex vivo the numbers of human hematopoietic stem cells (HSCs) without compromising their marrow repopulating capacity and their ability to establish multilineage hematopoiesis has been the subject of intense investigation. Although most such efforts have focused on cord blood HSCs, few have been applied to adult HSCs, a more clinically relevant HSC source for gene modification. To date, the strategies that have been used to expand adult HSCs have resulted in modest effects or HSCs with lineage bias and a limited ability to generate T cells in vivo. We previously reported that culturing umbilical cord blood CD34+ cells in serum‐free media supplemented with valproic acid (VPA), a histone deacetylase inhibitor, and a combination of cytokines led to the expansion of the numbers of fully functional HSCs. In the present study, we used this same approach to expand the numbers of adult human CD34+ cells isolated from mobilized peripheral blood and bone marrow. This approach resulted in a significant increase in the numbers of phenotypically defined HSCs (CD34+CD45RA‐CD90+D49f+). Cells incubated with VPA also exhibited increased aldehyde dehydrogenase activity and decreased mitochondrial membrane potential, each functional markers of HSCs. Grafts harvested from VPA‐treated cultures were able to engraft in immune‐deficient mice and, importantly, to generate cellular progeny belonging to each hematopoietic lineage in similar proportion to that observed with unmanipulated CD34+ cells. These data support the utility of VPA‐mediated ex vivo HSC expansion for gene modification of adult HSCs. Valproic acid (VPA)‐mediated ex vivo expansion of adult bone marrow and mobilized peripheral blood CD34+ cells resulted in a cellular product characterized by high viability, enrichment with CD34+CD45RA‐CD90+ cells, increased aldehyde dehydrogenase (ALDH) activity, robust multipotent clonogenic potential, and decreased mitochondrial potential. VPA‐expanded grafts were able to establish unbiased multilineage human hematopoietic‐cell chimerism in NSG mice at 16 weeks post‐transplantation.